HUBUNGAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM (PAI) DENGAN MOTIVASI BELAJAR SISWA DI SMP NURUL YAQIN PAMIJAHAN BOGOR - Nur'aeni, Ika; Nugraha, Acep; ihsan, Muzhir Ihsan (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
In the educational process, many factors are required to cultivate students' learning motivation, among which teachers play a dominant role as their guides. Throughout the teaching process, students can observe and actively participate in the learning process. Based on research findings, it was found that: (1) Based on the frequency distribution calculation regarding the level of teachers' professionalism, it was categorized as moderate at SMP Nurul Yaqin Pamijahan, Bogor. This can be seen from the number of respondents, 12 out of 30 respondents were in the interval 122-111. The presence of respondents in the interval 110-99 indicates the low or insufficient professionalism of religious teachers in the eyes of students. Meanwhile, students' learning motivation is also at a moderate level. This can be seen from the responses provided by 15 out of 30 respondents who were the research samples, falling within the interval 100-89; (2) There is a moderately positive relationship between the professionalism of Islamic Education teachers and students' learning motivation, with a correlation coefficient of 0.622. This value reflects that the professionalism of Islamic Education teachers and students' learning motivation have a moderate quantitative relationship. It means that teacher professionalism is not the only factor influencing students' learning motivation, as there are many other contributing factors.